Reviews (Reviews in religion and theology, 2002)
Books reviewed: Michael W. Myers, Brahman: A Comparative Theology Leo G. Perdue (ed.), The Blackwell Companion to the Hebrew Bible W. Lee Humphreys, The Character of God in the Book of Genesis: A Narrative Appraisal Klaus Baltzer, Deutero-Isaiah, Hermeneia — A Critical and Historical Commentary on the Bible Brevard S. Childs, Isaiah, The Old Testament Library Tina Beattie, The Last Supper According to Mary and Martha Jacob Neusner, The Halakhah and the Aggadah: Theological Perspectives J. Behr, Asceticism and Anthropology in Irenaeus and Clement John Chrysostom, Wendy Mayer and Pauline Allen, The Early Church Fathers Norman Russell, Cyril of Alexandria Carolinne White, Early Christian Latin Poets Phillip Cary, Augustine’s Invention of the Inner Self: The Legacy of a Christian Platonist Paul M. Collins, Trinitarian Theology West and East: Karl Barth, the Cappadocian Fathers, and John Zizioulas G. R. Evans (ed.), The Medieval Theologians: An Introduction to Theology in the Medieval Period Donald K. McKim, Introducing the Reformed Faith: Biblical Revelation, Christian Tradition, Contemporary Significance Eric L. Santner, On the Psychotheology of Everyday Life, Reflections on Freud and Rosenzweig Dietrich Bonhoeffer, The Cost of Discipleship John Robinson, Honest to God Gustavo Gutiérrez, A Theology of Liberation: History, Politics, and Salvation Vincent J. Donovan, Christianity Rediscovered: An Epistle from the Masai L. William Countryman, Dirt, Greed and Sex: Sexual Ethics in the New Testament and their Implications for Today Gerd Theissen, The Shadow of the Galilean: The Quest of the Historical Jesus in Narrative Form Anthony B. Pinn and Benjamin Valentin (eds), The Ties that Bind: African American and Hispanic American/ Latino/a Theologies in Dialogue Colin Gunton, The Christian Faith: An Introduction to Christian Doctrine Jacques Derrida, edited by Pascale-Anne Brault and Michael Naas, The Work of Mourning Juliet Floyd and Sanford Shieh (eds), Future Pasts: The Analytic Tradition in Twentieth-Century Philosophy John Hick, Dialogues in the Philosophy of Religion Michael Ruse, Can a Darwinian be a Christian? The Relationship Between Science and Religion Janet Radcliffe Richards, Human Nature After Darwin: A Philosophical Introduction